Evaluation of a transgender health training program for pharmacists and pharmacy students in Australia: A pre-post study - Swapna Chaudhary; Daniel Lindsay; Robin Ray; Beverley D. Glass (Elsevier, 2024)
Background: Disparities in healthcare for transgender and gender diverse (TGD) people are well-recognized, with pharmacists reporting a lack of knowledge impacting confidence in their interactions with TGD people. Therefore, a training program in TGD healthcare was designed to address this knowledge gap. Objective: To evaluate the impact of the TGD healthcare training program on the awareness, knowledge, and behaviour of pharmacists and pharmacy students in Australia. Method: An online training program was evaluated by pre-and post-test surveys, which assessed the knowledge and awareness of participants, and three-month post-training interviews, which examined the effect of training on pharmacists' practice when providing care to TGD people. Data were analyzed using paired t-tests, content and thematic analysis. Result: Fifty-six pharmacists and twenty-one pharmacy students completed the training and pre-and post-test surveys. Ten pharmacists were interviewed post-training. There was a significant improvement in the awareness (pharmacists, p ≤0.001; students, p = 0.006), knowledge (pharmacists and students, p ≤0.001) and total (pharmacists and students, p ≤0.001) post-test scores for both groups. Interviewed participants found the training program comprehensive and relevant to their practice. Conclusion: This study has demonstrated that educational interventions improve TGD healthcare awareness and knowledge for pharmacists and students with the potential to improve healthcare provision to TGD people and promote inclusivity in society.